Relationships between triathlon performance and pacing strategy during the run in an international competition - Le Meur, Y.; Bernard, T.; Dorel, S.; Abbiss, C. R.; Honnorat, G.; Brisswalter, J.; Hausswirth, C. (International Journal of Sports Physiology and Performance, 2011)
Purpose: The purpose of the present study was to examine relationships between athlete`s pacing strategies and running performance during an international triathlon competition. Methods: Running split times for each of the 107 finishers of the 2009 European Triathlon Championships (42 females and 65 males) were determined with the use of a digital synchronized video analysis system. Five cameras were placed at various positions of the running circuit (4 laps of 2.42 km). Running speed and an index of running speed variability (IRSVrace) were subsequently calculated over each section or running split. Results: Mean running speed over the first 1272 m of lap 1 was 0.76 km/h (+4.4%) and 1.00 km/h (+5.6%) faster than the mean running speed over the same section during the three last laps, for females and males, respectively (P < .001). A significant inverse correlation was observed between RSrace and IRSVrace for all triathletes (females r = -0.41, P = .009; males r = -0.65, P = .002; and whole population -0.76, P = .001). Females demonstrated higher IRSVrace compared with men (6.1 ± 0.5 km/h and 4.0 ± 1.4 km/h, for females and males, respectively, P = .001) due to greater decrease in running speed over uphill sections. Conclusions: Pacing during the run appears to play a key role in high-level triathlon performance. Elite triathletes should reduce their initial running speed during international competitions, even if high levels of motivation and direct opponents lead them to adopt an aggressive strategy.